Spatio-temporal variation of roadkills show mass mortality events for amphibians in a highly trafficked road adjacent to a national park, Costa Rica - Arevalo, Jose Edgardo (2017)
Roads have detrimental impacts on wildlife populations around the world. Specifically, roads pose direct and indirect threats to wildlife by limiting dispersal movements or through vehicle-related mortality. The rate of wildlife mortality varies both in time and space depending on the landscape composition and the type and use of road infrastructure. The objective of this study was to investigate spatiotemporal variation of vertebrate mortality in a 4km segment of the 34 national road, adjacent to Carara National Park, Costa Rica. We conducted 81 roadkill surveys by car and bicycle from June 2010 to May 2011, georeferenced the locations of the kills and identified them to the lowest possible taxonomic level. We recorded a total of 4 709 road-killed animals of at least 58 species of vertebrates during the whole study. Amphibians accounted for 93.5 % of all the vertebrate losses and showed strong spatiotemporal variation of mass mortality events. Reptiles, especially snakes, were the second most affected taxon followed by mammals and birds. Relative mortality per day in the 4 km segment was 125.4 amphibians, 4.6 reptiles, 2.7 mammals, 1 bird and 0.46 undetermined. Road proximity to the border of the park, traffic volumes and lack of enforcement of speed limits may influence the high rate of roadkills found. We suggest the reinforcement of speed limits, wildlife crossing signage and the retrofitting of the existing culverts as under passes for animals to minimize vertebrate mortality at the road adjacent to Carara National Park.